Problem-Based Learning in Malaysian Technical School - Mustapha, Ramlee; Abdul Rahim, Zaharatul Laila (EDUCARE, 2011)
ABSTRACT: The purpose of this action research was to identify the problems faced by electrical and electronic engineering or PKEE (Pelajaran Kejuruteraan Eelektronik dan Elektrik) students studying a difficult topic â transistor. This study was also aimed at examining studentsâ attitude towards Problem-based Learning (PBL). PBL is said to enhance studentsâ understanding and make the learning more meaningful. This action research was based on Kemmis and McTaggart (1998) model. Jigsaw technique was also used in the first and second rounds of the study whereas the discussion technique was used in the third round. A sample of 30 Form 5 students from a Technical School Melaka, Malaysia was selected. The treatment was given for a nine-weeks duration. Data were obtained from peer assessment, observation, and pre- and post-tests. Descriptive statistics used in this study, include frequency, mean, and standard deviation. The study found that the collaboration skill of the students increases in each round and their achievements also show better results. Studentsâ attitude became more positive with regard to PBL. In the open-ended questions, the respondents said that they like collaborative and problem-solving activities. Thus, teachers are suggested to use this method. However, for those who are not confident or do not have the skills to use the PBL method, it is advised that training and guidance be given to them. PBL workshops and short courses should be offered to them.KEY WORDS: Action research, problem-based learning, jigsaw technique, electrical and electronic engineering, and technical school.About the Authors: Prof. Dr. Ramlee Mustapha and Zaharatul Laila Abdul Rahim are Lecturers at the Faculty of Technical and Vocational Education UPSI (Sultan Idris University of Education), Tanjong Malim, Perak Darul Ridzuan, Malaysia. One of the authors can be reached at: drramlee@yahoo.comHow to cite this article? Mustapha, Ramlee & Zaharatul Laila Abdul Rahim. (2011). âProblem-Based Learning in Malaysian Technical Schoolâ in EDUCARE: International Journal for Educational Studies, Vol.4(1) August, pp.41-54. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 1, 2011); Revised (July 2, 2011); and Published (August 17, 2011).